Entrepreneurial Readiness among University Students: Implications for Higher Education Development - Suhaeb, Sutarsi; Djawad, Yasser Abd.; Sabara, Edy (International Journal of Technology and Education Research, 2025)
This study aims to analyze the level of entrepreneurial readiness among university students, focusing on key indicators such as entrepreneurial motivation, knowledge, managerial skills, organizational or work experience, and environmental support. The research employed a quantitative approach with a descriptive research design to provide an objective and measurable overview of students’ readiness for entrepreneurship. The population consisted of all active students at the selected university, and a sample of 275 students was obtained using proportional random sampling. Data were collected using a structured, closed-ended questionnaire with a five-point Likert scale. The results revealed that the majority of students demonstrated a high level of entrepreneurial readiness, with 79.27% in the high category and 4.73% in the very high category, while 16.00% were in the moderate category. No respondents fell into the low or very low categories, indicating that all students possessed at least a moderate level of readiness. These findings suggest that students generally have adequate motivation, knowledge, skills, and environmental support to initiate entrepreneurial activities. The high readiness levels may also reflect the effectiveness of entrepreneurship education programs implemented by higher education institutions. Nevertheless, the presence of students in the moderate category indicates a need for further development, particularly in enhancing practical experience, risk-taking ability, and direct business exposure. Therefore, targeted interventions such as mentoring, practice-based entrepreneurship training, and business network expansion are recommended to elevate students’ readiness to a higher level.